Exploring the effect of ambient crowdedness on eating behaviors : an experimental study - Sam, Joyce Yan Ting (2018)
Eating behaviors are influenced by a confluence of sensory (e.g., ambient lighting), normative (e.g., social facilitation), and emotional (e.g., stress) factors. Given the issue of increasing obesity rates and human crowding in Singapore, we explored the effects of a common environmental factor that has received lesser attention – ambient crowdedness – on food consumption and eating rate. We hypothesize that a crowded dining environment will produce greater food intake and faster eating rate than an uncrowded dining environment due to various reasons. Since crowded environments activate low-level construals, individuals may consume a greater quantity of food as they focus more on its secondary (e.g., palatability) instead of primary (e.g., health implications) features. As fast-tempo music accelerates eating speed, individuals may also eat faster given that background noise in crowded environments is typically of a higher frequency. In a between-subject design, 80 Nanyang Technological University (NTU) undergraduates were provided with an ad libitum pasta lunch either in a crowded or uncrowded campus canteen. Pre- and post- consumption measurements of the pasta were taken to ascertain food intake while meal duration was recorded to determine eating rate (g/s). Contrary to our prediction, analyses revealed no statistically significant differences between crowded and uncrowded dining environments on food intake and eating rate. Consequently, the findings demonstrate that environmental crowdedness has no significant effect on food intake and eating rate. Given that overconsumption and fast eating speeds may lead to obesity, more research is required to better understand the impact that environmental crowdedness has on eating behaviors.